2020
DOI: 10.1073/pnas.1918944117
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical nuclear localization signals mediate nuclear import of CIRBP

Abstract: The specific interaction of importins with nuclear localization signals (NLSs) of cargo proteins not only mediates nuclear import but also, prevents their aberrant phase separation and stress granule recruitment in the cytoplasm. The importin Transportin-1 (TNPO1) plays a key role in the (patho-)physiology of both processes. Here, we report that both TNPO1 and Transportin-3 (TNPO3) recognize two nonclassical NLSs within the cold-inducible RNA-binding protein (CIRBP). Our biophysical investigations show that TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 85 publications
(116 reference statements)
5
69
0
Order By: Relevance
“…The ZnF domain of FUS does not interact with Kapβ2 and the interaction with FUS(R495X) appears to be mediated by both the RGG2 and RGG3 regions. The binding preference of RGG regions to importins is not 34 . Therefore, Kapβ2 and probably other importins may interact with RGG regions using many different modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ZnF domain of FUS does not interact with Kapβ2 and the interaction with FUS(R495X) appears to be mediated by both the RGG2 and RGG3 regions. The binding preference of RGG regions to importins is not 34 . Therefore, Kapβ2 and probably other importins may interact with RGG regions using many different modes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that when the PY-NLS of FL-FUS occupies Kapβ2′s PY-NLS binding site (K D ~ 30 nM), the FUS RGG regions bind weakly and dynamically to site(s) outside of the PY-NLS binding site of Kapβ2 18 . Interestingly, Bourgeois et al recently reported that the acidic loop of Kapβ2 interacts with RGG regions of cold-inducible RNA-binding protein, CIRBP 34 . Therefore, Kapβ2 and probably other importins may interact with RGG regions using many different modes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the import of PY-NLS-containing cargoes, Trn1 is implicated in the import of various cargoes obviously lacking a PY-NLS ( Twyffels et al, 2014 ; Chook and Süel, 2011 ). These cargoes are imported by Trn1 via non-PY-NLSs, and include diverse proteins such as the core histones (H2A, H2B, H3 and H4) ( Mühlhäusser et al, 2001 ; Baake et al, 2001 ; Mosammaparast et al, 2002 ; Blackwell et al, 2007 ; Soniat et al, 2016 ), ribosomal proteins (RPL23A, RPL5, RPL7 and RPS7) ( Jäkel and Görlich, 1998 ; Tai et al, 2013 ), viral proteins ( Arnold et al, 2006 ; Le Roux and Moroianu, 2003 ; Klucevsek et al, 2006 ), the RNA-editing enzyme ADAR1 ( Fritz et al, 2009 ; Barraud et al, 2014 ; Banerjee and Barraud, 2014 ), the transcription factor FOXO4 ( Putker et al, 2013 ), and the cold-inducible RNA-binding protein CIRBP ( Bourgeois et al, 2020 ). With some exceptions, PY-NLS seem to be specific to Trn1, while non-PY-NLS can be imported by Trn1 but can frequently be recognized and imported by multiple karyopherins such as the heterodimer Impα/Impβ ( Kimura et al, 2013 ; Twyffels et al, 2014 ).…”
Section: Nuclear Localization Signal Recognition By Transportin-1mentioning
confidence: 99%
“…In another recent report, a non-PY-NLS has been identified in the cold-inducible RNA-binding protein CIRBP and was shown to participate in the Trn1-mediated nuclear import of CIRBP ( Bourgeois et al, 2020 ). This non-PY-NLS corresponds to a ∼40-residue region rich in RG and RGG motifs, called the RG/RGG region.…”
Section: Nuclear Localization Signal Recognition By Transportin-1mentioning
confidence: 99%
“…Other known NLSs/NESs that bind directly to Impβ family are: the PY-NLS for Trn1 and Trn2 (Lee et al, 2006), the Leu-rich NES for CRM1 (Hutten and Kehlenbach, 2007), the SR-domain for TrnSR (Maertens et al, 2014), and the β-like importin binding (BIB)-domain, which binds to several nucleocytoplasmic transport receptors (Jäkel and Görlich, 1998). In addition, the RG/RGG-rich segment for Trn1 and the RSY-rich segment for TrnSR were reported recently (Bourgeois et al, 2020). However, these known NLSs/NESs do not explain all of the cargo recognition sites.…”
Section: Prediction Of Nuclear Localization Signals and Nuclear Expormentioning
confidence: 99%